Analisis Keefektifan Kalimat pada Teks Laporan Hasil Observasi di Modul Pembelajaran Bahasa Indonesia Tingkat SMA Kelas X yang Disusun oleh Indri Anatya Permatasari, M.Pd. sebagai Kelayakan Bahan Ajar Membaca Pemahaman - Arsya Ramadhani; Dini Sustiani; Ikhwatika Putri Hardiansah; Kalista Fitri Maharani; Nazhifa Destrianti Farradina; Asep Purwo Yudi Utomo; Rina Sari Madyaningtyas (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The Indonesian language learning module for high school X-grade students, created by Indri Anatya Permatasari, M.Pd, contains several writing errors. These errors include inconsistencies in punctuation marks, diction, conjunctions, and inappropriate meaning, which do not align with the norms of good and correct language usage. Effective sentence structure is crucial for conveying information clearly to readers. The discovery of these errors in the observation report text within the module prompted further research. The research aims to identify and address these writing errors to improve the module and enhance students' comprehension of the text. By analyzing these errors, the learning module can be tailored to better meet the needs of the students. The research adopts a qualitative descriptive approach, with the observation report text within the Indonesian language learning module as the primary data source. The method involves thorough reading of the text, error identification, analysis, categorization, and correction. The observation report text contains facts gathered from observation activities. The research revealed four writing errors: inconsistencies in the use of punctuation marks, diction, conjunctions, and inappropriate meaning. These errors are attributed to the author's limited knowledge and skills in report writing.